2013
DOI: 10.22437/jiseb.v16i2.2782
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Perkebunan Kelapa Sawit Dalam Pembangunan Ekonomi Wilayah Di Kabupaten Muaro Jambi

Abstract: Penelitian ini bertujuan untuk (1) mengetahui potensi ekonomi perkebunan kelapa sawit di Kabupaten Muaro Jambi dilihat dari aspek pendapatan dan aspek tenaga kerja, (2) untuk mengetahui besar dampak dari perkebunan kelapa sawit terhadap total pendapatan dan total tenaga kerja di Kabupaten Muaro Jambi. Metode analisis yang digunakan adalah analisis sektor basis dengan menggunakan formulasi Location Quotien (LQ), analisis shift share, analisis multiplier dan analisis kontribusi. Berdasarkan hasil penelitian dipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The higher the production of plantation crops, the higher the agricultural sector's economic growth, contributing to Indonesia's income. The findings of this study are supported by research indicating that plantation crop production has a significant effect on the GRDP of the agricultural sector [4,6,[13][14][15]. Oil palm is the plantation crop that contributes the most to the agriculture sector's GRDP [9].…”
Section: The Effect Of Plantation Crop Production On the Agrigrdpsupporting
confidence: 62%
See 1 more Smart Citation
“…The higher the production of plantation crops, the higher the agricultural sector's economic growth, contributing to Indonesia's income. The findings of this study are supported by research indicating that plantation crop production has a significant effect on the GRDP of the agricultural sector [4,6,[13][14][15]. Oil palm is the plantation crop that contributes the most to the agriculture sector's GRDP [9].…”
Section: The Effect Of Plantation Crop Production On the Agrigrdpsupporting
confidence: 62%
“…These conditions do not necessarily affect the growth of AgriGRDP. AgriGRDP is significantly influenced by plantation crop production (PPC) [4,6,[13][14][15]. Food crop production (PFC), which includes rice, corn, soybeans, and other crops, significantly affects AgriGRDP [5,6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the controversy, the development of oil palm plantations has brought economic benefits to many rural communities in Jambi, including job opportunities and increased income. For example, it has induced high absorption of regional labor-in the case of Muaro Jambi Regency, labor absorption reached 28.41% [96]-and has provided a multiplier effect for GRDP [97]. Mara and Fitri [97] found that every increase in income in the palm oil sector of IDR 1 (Indonesian rupiah) will result in an increase in the village's GRDP of IDR 1.417.…”
Section: Policies Inducing Development Progressmentioning
confidence: 99%
“…Economic activities related to the oil palm sector are divided into production, consumption and general distribution in a supply chain. The oil palm sector's potential is reflected in the aspects of earnings and labor (Christiani, Mara, & naenggolan, 2013). The economic potential of this sector lies in how the added-value flow starts in the oil palm supply system or from the procurement of fresh fruit bunch (FFB) at an oil palm plantation.…”
Section: Oil Palm Sector Linkmentioning
confidence: 99%